EXPLORING UNDERGRADUATE STUDENTS’ PERCEPTION OF THE BENEFITS AND DRAWBACKS IN DISTANCE LEARNING DUE TO COVID-19 PANDEMIC - Atikah Wati; Kardi Nurhadi; Rezky Nugraha Tsani (Universitas Sarjanawiyata Tamansiswa, 2021)
This present research focused on exploring undergraduate students’ perception of distance learning in terms of experiences, benefits, and drawbacks (time management, cost, technical difficulties). It was grounded in a qualitative approach with a phenomenological case study design. Three undergraduate students of the 9th semester from the English Education Department in Wiralodra University were recruited to participate in this research. The data were derived from the three-interview series framework that consists of fifteen questions. The interview data were qualitatively analyzed by using inductive phenomenological reduction based on Seidman (2013). This research revealed that undergraduate experience varies, from the struggle with the connection to the limited communication between lecturer-students or student-students. Distance learning also impacts their feeling on how they mean distance learning, which makes the students mostly lazier as the communication is also limited and the policy is none to them who are not attending the class. It is also showed benefits and drawbacks where it is more flexible but unstable. The cost comes to be cheaper, but they still pay the tuition fee even though they did not use the campus facility, and the main technical difficulties lie in which device and apps they used at that moment. Keywords: perception, distance learning, benefits, drawbacks.